2022
DOI: 10.1108/jsbed-07-2021-0274
|View full text |Cite
|
Sign up to set email alerts
|

Job challenges are hindrances too: examining experiences of managers and employees in Finnish SMEs

Abstract: PurposeThe study aims to explore job demands experienced by employees and managers in micro-enterprises and small and medium-sized enterprises (SMEs). Drawing on the job demands framework, the study discusses the experienced demands from the perspective of challenges that create opportunities for learning and achievement and hindrances that create obstacles for work. The study builds on the idea that the same demand can be perceived both as a challenge and a hindrance. That approach opens a path to responding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This is because these enterprises constitute intense, close and casual working relations among employees and owner-managers (Cu ellar-molina et al, 2019). Relatedly, since micro enterprises are characterized by insufficient resources, less market control and informality, their leverage lies in the kind of relationships created between individuals (Al Mamun et al, 2018;Vanharanta et al, 2022). In these enterprises, people confide in others, support one another, create friendly ties and work harmoniously (Mascarenhas et al, 2010;Shier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because these enterprises constitute intense, close and casual working relations among employees and owner-managers (Cu ellar-molina et al, 2019). Relatedly, since micro enterprises are characterized by insufficient resources, less market control and informality, their leverage lies in the kind of relationships created between individuals (Al Mamun et al, 2018;Vanharanta et al, 2022). In these enterprises, people confide in others, support one another, create friendly ties and work harmoniously (Mascarenhas et al, 2010;Shier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, since micro enterprises are characterized by insufficient resources, less market control and informality, their leverage lies in the kind of relationships created between individuals (Al Mamun et al. , 2018; Vanharanta et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristics of SME employees, who often contend with heavy workloads [104], overtime demands, and various administrative responsibilities, participants in the study expressed that their job roles contributed to persistent feelings of depression, anxiety, stress, and other mental health issues [105], even amid the pandemic. While meaningful work seems to act as a protective factor, there has been no research exploring whether it can mitigate the impact of stress and enhance the mental health of SME employees during the COVID-19 pandemic.…”
Section: Meaning Making Through Workmentioning
confidence: 99%
“…The qualitative study of Mousa and Samara (2022) revealed that employees who can do meaningful work may experience less stress and have better mental health. Considering the nature of SME employees, who are needed to handle a heavy workload (Vanharanta et al, 2022), work overtime, and perform other admin duties, the participants claimed that their job duties caused them to experience constant depression, anxiety, stress, and other mental disorders (Chhinzer, 2022). Although meaningful work appears to be a protective factor, no research has been done to investigate if it may mitigate the impacts of stress and enhance the mental health of SME employees.…”
Section: Meaningful Work and Mental Healthmentioning
confidence: 99%